Early treatment with rutoside and ascorbic acid is highly effective for progressive pigmented purpuric dermatosis. (December 2014) - Schober, Sarah M.; Peitsch, Wiebke K.; Bonsmann, Gisela; Metze, Dieter; Thomas, Kai; Goerge, Tobias; Luger, Thomas A.; Schneider, Stefan W.
Summary Background and Objectives Progressive pigmented purpuric dermatosis (PPPD, Schamberg disease) is a rare benign, but chronic dermatosis frequently misdiagnosed as vasculitis or bleeding disorder. Although affected patients experience significant impairment in quality of life no effective treatment has been established. The aim of our two center case series was to evaluate efficacy and tolerability of the antioxidants rutoside and ascorbic acid as combination treatment for PPPD. Patients and Methods A retrospective review was performed on 35 patients with PPPD treated with 2 × 50 mg rutoside and 1 000 mg ascorbic acid daily between 2004 until 2011. The mean treatment duration was 8.2 months. Results 71.4 % of the participants experienced complete clearance and 20.0 % an improvement of more than 50 %, accompanied by increased quality of life. Nine participants (25.1 %) relapsed after discontinuation. In seven, rutoside and ascorbic acid was re‐initiated, and all responded again. Only three participants reported mild adverse effects. Participants with shorter disease duration showed better therapeutic success, shorter time to response and lower risk of recurrence. Conclusion Oral rutoside and ascorbic acid may be an efficient and well tolerated treatment for PPPD. Early treatment is recommended to achieve best clinical outcome.